Shape memory alloy preparation for multiaxial tests and identification of fundamental alloy performance - Tanaka, K.; Kitamura, K.; Miyazaki, S. (Archives of Mechanics, 1999)
TiNi shape memory alloy preparation for the multiaxial tests was explained. Stable response of the alloy was realized, not by training but by an effective combination of the alloying technique and the heat treatment: Ti-51.0at%Ni polycrystalline shape memory alloy heat-treated by annealing at 673 K for 3.6 ks followed by cooling in a furnace. Some preliminary tests were performed to identify the fundamental alloy characteristics: the transformation temperatures, the stress-strain curves at several temperatures and the strain-temperature curves under constant hold stresses.